can you please prove it.
Attachments:
![](https://hi-static.z-dn.net/files/d57/a075f6e5171f17aab19cf241c9b0a409.jpg)
Answers
Answered by
0
Answer:
Step-by-step explanation:
Firstly,
Construction..
Join XC, AC and BC..
Therefore Angle AXC = 90 degree
(angle in a semicircle), Thus, also Angle BXC = 90 degree -----------(1)
Now in ΔAXC and ΔBXC
CX = CX. (common)
angle AXC = angle BXC [From (1)]
AC = BC (radius of bigger circle)
Therefore,
Δ AXC congruent to ΔBXC
(By SAS comgruency axiom)
AX = BX (cpct)
Thus proved.....
Similar questions